RELATIONSHIP OF STEREOMETRY AND PLANIMETRY DEPARTMENTS OF GEOMETRY (Web of Teachers: Inderscience Research, 2023)
In this article, we will work on the study of the stereometry and planimetry sections of the general secondary school geometry science and the role of the science in increasing the thinking level of students.